Effect of surfactant species and electrophoretic medium composition on the electrophoretic behavior of neutral and water‐insoluble linear synthetic polymers in nonaqueous capillary zone electrophoresis. Issue 13 (11th May 2017) - Fukai, Nao; Kitagawa, Shinya; Ohtani, Hajime
Abstract : We have recently demonstrated the separation of neutral and water‐insoluble linear synthetic polymers in nonaqueous capillary zone electrophoresis (NACZE) using a cationic surfactant of cetyltrimethylammonium chloride (CTAC). In this study, eight ionic surfactants were investigated for the separation of four synthetic polymers (polystyrene, polymethylmethacrylates, polybutadiene, and polycarbonate); only three surfactants (CTAC, dimethyldioctadecylammonium bromide, and sodium dodecylsulfate) caused their separation. The order of the interaction between the polymers and the surfactants depended on both the surfactant species and the composition of the electrophoretic medium. Their investigation revealed that the separation is majorly affected by the hydrophobic interactions between the polymers and the ionic surfactants. In addition, the electrophoretic behavior of polycarbonate suggested that electrostatic interaction also affects the selectivity of the polymers.